Interdisciplinarity and intersectoriality in the Family Health Strategy and Nuclei of Support to Family Health: potentialities and challenges - Luís Felipe Ferro; Emelin Cristina da Silva; Ana Beatriz Zimmermann; Regina Célia Titotto Castanharo; Fernanda Rodrigues Leite de Oliveira (O Mundo da Saúde)
The Family Health Strategy (ESF) was implanted in order to reorient the health care model through the development of activities to promote health, prevent illness, recovery and rehabilitation with focus on the individual, the family and the community. To support ESF, the Ministry of Health created, in 2008, the Nuclei of Support to Family Health (NASF). NASF, composed by different professionals, aim to increase the scope of ESF actions and its outcomes, working in cooperation with the family health teams. In this context, this study aims to understand the potentials and difficulties regarding the practice of interdisciplinary and intersectorial actions by ESF e NASF professionals of a Primary Care Unity of Curitiba. Through a qualitative-exploratory field research, 12 professionals from ESF and NASF were interviewed from November 2011 to January 2012. Data were analyzed by using a hermeneutic-dialectic method. The subjects underlined the value of interdisciplinary and intersectorial practice. However, some reports expressed a certain fragmentation of the work due to the valorization of knowledge specialization. Still some reports highlighted as barriers: the excessive demand of work; the restriction of communication among other sectors and equipments to referrals and occasional telephone calls; the lack of interest of certain equipments as regards working together. Thus, we underline the need for new strategies that promote formal meetings among professionals from different social equipments for developing effective actions.